Bergenin glycosides from Rodgersia aesculifolia. (September 2015) - Zhang, Hui; Su, Yanfang; Wu, Zhenhai; Gao, Xiumei
Graphical abstract: Structures of three bergenin glycosides (1 –3 ) together with twenty known compounds from Rodgersia aesculifolia were elucidated on the basis of spectroscopic analysis. Highlights: 3 bergenin glycosides and 20 known compounds were isolated from R. aesculifolia . Structures were determined by 2D NMR, IR and HRMS. This is the first report of bergenin glycosides from nature. Abstract: Phytochemical investigation on Rodgersia aesculifolia afforded twenty-three compounds, including three bergenin glycosides, previously unknown in nature, together with twenty known compounds. Their structures were elucidated by the extensive use of 1D and 2D NMR experiments, along with IR and HRESIMS spectra. This is the first report of bergenin glycosides from nature.